1988
DOI: 10.1080/01904168809363808
|View full text |Cite
|
Sign up to set email alerts
|

Role of water stress in differential aluminum tolerance of two barley cultivars grown in an acid soil

Abstract: Two cultivars of barley (Hordeum vulgare L.), Al-sensitive 'Dayton' and Al-tolerant 'Kearney', were grown under controlled environmental conditions to determine the influence of Al stress and water stress imposed separately and in combination with one another. Plants were grown for 4 weeks in polyethylene-lined, waxed cartons containing 1 kg of acid, Al-toxic, Tatum subsoil (clayey, mixed, thermic, Typic Hapludult) at high (pH 4.7) or low (pH 6.6) Al stress. During the final 2 weeks they were also subjected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…Seminal (axial) root growth was more resistant to soil acidity than other components of the root system, and this appears to be particularly important in moisture-limited environments where survival of perennial species depends upon establishing their roots in moist subsoil before the onset of drought conditions. Indeed, drier conditions exacerbate differences between acid-soil sensitive and resistant genotypes, with the better root growth of acid-soil resistant genotypes aiding water extraction (Krizek and Foy 1988;Tang et al 2002). Survival of sensitive species such as tall wheatgrass, for which the seminal root length was restricted in all three soils, is often compromised in the field (Culvenor et al 2004).…”
Section: Implications Of Responses For the Fieldmentioning
confidence: 99%
“…Seminal (axial) root growth was more resistant to soil acidity than other components of the root system, and this appears to be particularly important in moisture-limited environments where survival of perennial species depends upon establishing their roots in moist subsoil before the onset of drought conditions. Indeed, drier conditions exacerbate differences between acid-soil sensitive and resistant genotypes, with the better root growth of acid-soil resistant genotypes aiding water extraction (Krizek and Foy 1988;Tang et al 2002). Survival of sensitive species such as tall wheatgrass, for which the seminal root length was restricted in all three soils, is often compromised in the field (Culvenor et al 2004).…”
Section: Implications Of Responses For the Fieldmentioning
confidence: 99%
“…In Scots pine and Norway spruce, water deficit more strongly reduced the root elongation-rate and numbers of growing roots in a soil with pH 3.8 and high levels of Al than in a pH 5.9 soil and lower Al levels (Bartsch 1987). Krizek and Foy (1988a) and Krizek et al (1988) observed that drought exacerbated the effects of Al toxicity in plants, and increasing the soil-moisture level reduced Al toxicity in barley (Hordeum vulgare L.) and sunflower (Helianthus annuus L.). Schier and McQuattie (2000) found that at low soil moisture the growth of ectomycorrhizal pitch pine (Pinus rigida Mill.)…”
Section: Root-growth Response Of Plants To Aluminium Toxicity and Dromentioning
confidence: 99%
“…Aluminum toxicity inhibits root cell division and elongation, thus reducing water and nutrient uptake and grain yield (Reid, 1971;Alam, 1981;Foy, 1983). Reduced drought tolerance, winter hardiness, and disease resistance have been indirectly associated with Al toxicity (Foy, 1984;Krizek & Foy, 1988). In Brazil, where toxic levels of Al occur in over half of the agricultural areas (Iturri Larach & Camargo, 1976), barley production is limited to limed soils.…”
Section: Análise Genética Da Tolerância Ao Alumínio Em Cevadas Brasilmentioning
confidence: 99%